Investigation on energy efficiency of lighting system in a university library - Ahmad Jasmi, Siti Zulaiha; Ayob, Mohd Fairullazi; Aripin, Srazali; Mohd Rahim, Faizul Azli (2019)
The electrical lighting system is one of the most significant contributors to energy consumption and operational cost for a library building. The extended operation of the lighting system in the library building consumes a high amount of energy, which requires the adoption of energy efficiency implementation to reduce energy consumption and to overcome energy waste. The objective of this paper is to present the outcomes of investigation on the energy efficiency of the lighting system in a university library building. The lighting system operated in a library building in one of the universities in Malaysia was chosen as the subject of the case study. A semi-structured face to face interview was carried out to interview four respondents who currently in-charge in the lighting system operation of university library building under the study. Looking at the results of the study, the lighting system of the university library is not energy efficient which leads to high energy consumption. To overcome energy waste, the results revealed that a proper guideline for the adoption of energy efficiency and cost-effectiveness of the lighting system is essential to be developed by the university authority for the university library.